Assessing the impact of abiotic and biotic factors on seedling survival in an African montane forest - Abiem, Iveren; Kenfack, David; Chapman, Hazel M. (Frontiers in Forests and Global Change, 2023)
Tree seedling dynamics underpin subsequent forest structure and diversity as different species/guilds respond variously to abiotic and biotic stresses. Thus, understanding differential seedling responses to stresses helps us to predict forest trajectories. Because forests vary in both environment and species composition, generalisations across tropical forests are difficult. Afromontane forests are important carbon stores, harbour high diversity and provide critical ecosystem services, yet they are vulnerable to climate change. Here, we investigate the importance of key abiotic and biotic factors on survival of seedling guilds along spatial and temporal scales in a montane forest in south-eastern Nigeria. We use data from 318 seedling plots censused every 3 months from 2017 to 2020 to identify 7 key abiotic and four biotic factors influencing seedling survival. We used the Kaplan-Meier method to estimate the persistence time of 1145 seedlings at community and guild levels. At the community level, newly recruited seedlings had a median survival time of 15 months and about 37% of the seedlings sampled where still alive after 24 months. Understory tree species survived significantly longer than the other growth form guilds and seedling survival did not differ across shade tolerance guilds. Conspecific adult density and steeper, more north facing slopes had a negative effect on tree seedlings survival. In addition, tree seedlings that recruited in October (end of wet season/beginning of dry) had lower survival probabilities compared to those that recruited in the other months. Except for initial height, seedling survival in lianas was not impacted by any of the abiotic and biotic variables tested. Our results suggest that under the current environment forest structure and diversity is changing, most noticeably lianas are increasing in abundance relative to trees.